Literacy as an Effective Media for Distance Learning - Sinta Diana Martaulina; Selvie Sianipar; Riodinar Harianja (Edunesia : Jurnal Ilmiah Pendidikan, 2021)
The emergence of the phenomenon of distance learning as online learning during the pandemic is concerned about the quality of achieving learning objectives. Finally, distance learning becomes an option so that the implementation of higher education can still be carried out like conventional learning. This restlessness opens opportunities for literacy methods as an effective medium in distance learning. The purpose of this research is to explain that literacy is not limited to reading and writing skills. Familiarize students with reading and accessing information before learning is a positive habit for organizing the brain and critical analysis skills. The research method used in research during this pandemic is a literature study "library research" (library research) with a qualitative approach. The type of data used is secondary data obtained from various sources such as books, journals, scientific writings as well as observations of online learning at the research campus. The research findings refer to several references, that literacy is the local wisdom of the Indonesian people, has practical goals that can be utilized and developed as a renewal in the era of educational technology. Thus, during this pandemic, literacy has been developed in various aspects of learning life such as technology, culture, politics, finance, information, and so on. The impact of literacy effectively has made students able to study independently and learn actively. Mastery of technology in literacy creates student learners, thinkers, researchers, and agents of change. The use of literacy as a medium for distance learning is an opportunity that this learning provides an opportunity for anyone to learn. The effectiveness of literacy as a medium in distance learning is very important to be developed with the mastery of digital technology